FAKTOR YANG MEMENGARUHI KEJADIAN MALARIA DI WILAYAH KERJA PUSKESMAS LEUSER KABUPATEN ACEH TENGGARA PROVINSI ACEH TAHUN 2019 - Hermanto Putra (Jurnal Komunitas Kesehatan Masyarakat, 2020)
Malaria is an infectious disease transmitted by female Anopheles mosquitoes, affecting humans throughout the world. Malaria is one of the diseases that never disappear (emerging) which shows a trend of increasing cases in several countries. The purpose of this study is to analyze environmental factors, behavioral factors, biological environment and health service factors are factors that influence the incidence of malaria in the work area of ​​Leuser Health Center This research uses a quantitative type with a Case Control approach. The population in this study were those who suffered from malaria and those who did not suffer from malaria in Leuser Health Center in Southeast Aceh Regency in 2019 as many as 64 controls and 64 cases with the technique of random sampling. Data collection is carried out with primary, secondary and tertiary data. Data analysis was performed with univariate, bivariate (Chi Square test) and multivariate (multiple regression test) analyzes. The results showed that the air temperature factor with a Sig value of 0.722 and OR 0.827, the majority there was a puddle factor with a value of Sig 0.001 and OR 3.667, a Distance to Home factor with a Breading Place with a value of Sig 0.001 and OR 3.432, a cage factor for animals with a value of Sig 0.001 and OR 3,695, the lighting factor for the majority of malaria events <60 lux as many as 37 respondents (57.8%) who suffer and 38 respondents (59.4%) who do not suffer with a Sig value of 0.858 and OR 1.067, a House Wall factor with a sig value of 0.008 and OR 3,051, anti mosquito repellent factor with a sig value of 0.014 and OR 0.193, a habit factor at night out with a sig value of 1,000 and OR 0.860, an extension factor with a sig value of 0.042 and an OR of 2.945, a home spraying factor with a sig value of 0.204 and an OR 2.231 , and treatment factors with Sig values ​​0.030 and OR 5,073. The conclusion of this study is that there is an influence of waterlogging factors, the distance between the house and the breeding place, the presence of animal pens, house walls, the use of mosquito coils, counseling, and treatment of malaria. The most dominant variable on malaria incidence is standing water. It is expected that the regional and central government policies are expected to create a key goal in achieving the targets in preventing malaria, especially regarding water puddles that have become commonplace in the community in the Leuser Health Center in the Southeast Aceh District of Aceh Province.